Blended Method: Online-Offline Teaching And Learning, On Students’ Reading Achievement - Setyawan, Harits (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aimed at investigating the effect of Blended Method (online and offline teaching and learning) and Traditional Method (offline teaching and learning), as the comparison, on students’ reading achievement. There were 200 college students involved in this study. Half of them were taught through a blended teaching method and half of them were taught through a traditional teaching method. The data were taken from the students’ final scores in the lectures which included scores of assignment, quiz, mid-term test, and final term test. The final scores of the two groups were compared to find out the effect of the blended teaching method and the traditional teaching method. The result showed that the scores of students who were taught through Blended Method were significantly better than the scores of students who were taught through Traditional Method. It indicates that utilizing new methods while maintaining good aspects of pre-existing methods has a positive impact on students’ achievement